COVID-19 Gymnastics: An Exercise used for Adult Mental Health - Geraldi Novian; Komarudin; Sandey Tantra Paramitha; Muhammad Gilang Ramadha; Alen Rismayadi; Mochamad Yamin Saputra; Mona Fiametta Febrianty; Patriana Nurmansyah Awwaludin (Journal of Physical Education Health and Sport, 2024)
One of the psychological elements that is crucial to life’s journey is mental wellness. People that are mentally sick will suffer from bad effects in their lives. The purpose of this research is to certain how COVID-19 gymnastics implementation affects adult mental health. In this investigation, the experimental approach was applied by treating adults with COVID-19 gymnastics. There were 150 adults as subjects. The GHQ-12 is used as a tool to assess mental health. Data analysis was done using the t-test. The implementation of COVID-19 gymnastics has a major impact on adults’ mental health. Furthermore, this study revealed a rise in mental health scores. From this study, we can concluded that adult mental health can benefit from COVID-19 gymnastics. For a specific amount of time, this activity is implemented really successfully in order to have a greater long-term effect.